Editorial: Advances in wearable devices for sports - Morais, J.E. (2023)
In sports, coaches and support staff spend considerable time analyzing athletes’ tech- nique. It is well known that athletes who can perform movements associated with their sport of choice using a better technique are more likely to present better performances. Video-based analysis has traditionally been the most used procedure to assess athletes’ technique [1,2]. This consists of recording sports skills and the subsequent computation of meaningful parameters describing the movement from raw data [3]. However, this data acquisition and handling is a time-consuming process. Consequently, coaches and sup- port staff are looking for less time-consuming procedures that lead to real-time outputs and that they themselves can also use and handle. The use of wearables allows the acqui- sition of kinematic [4], kinetic [5], or physiological variables [6] that are of paramount im- portance for coaches and athletes. For instance, Lim et al. [7] aimed to predict the lower limb kinetics and kinematics during walking with a single inertial measurement unit (IMU) placed on the lower back. In the specific case of the aquatic environment, cable handling makes data collection more difficult. Thus, wearable usage is a solid alternative in aquatic sports. Besides kinematic data, swimming researchers can also measure kinetic parameters, such as propulsive force, that are key determinants for performance enhance- ment [5,8]. Regarding physiological parameters, these can also be measured or estimated with the data collected with wearables. A study by Dasa et al. [9] aimed to assess the ac- curacy of commonly used global positioning systems/accelerometer-based tracking de- vices to estimate energy expenditure during high-intensity intermittent exercise in soccer. The authors noted an underestimation of the energy expenditure since these gears do not account for anaerobic energy production during high-intensity exercise [9]. Nonetheless, and despite the deviations observed in energy expenditure that should be considered by practitioners and researchers, it was argued that the devices tested can still provide useful information, but with the limitations addressed.